Matilda - Dahl, Roald; Blake, Quentin (New York, N.Y. : Viking, 1988)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal starred, October 1988.
Child Study Children's Book Committee, January 2004.
New York Times, March 1996.
Horn Book, March 1995.
Keywords: Schools -- Fiction; Humorous stories; School stories; Humorous fiction; Schools -- Fiction